Electronic Raman scattering as an ultra-sensitive probe of strain effects in semiconductors - Fluegel, Brian (Nat Commun, 2015)
Semiconductor strain engineering has become a critical feature of high-performance electronics because of the significant device performance enhancements that it enables. These improvements, which emerge from strain-induced modifications to the electronic band structure, necessitate new ultra-sensitive tools to probe the strain in semiconductors. Here, we demonstrate that minute amounts of strain in thin semiconductor epilayers can be measured using electronic Raman scattering. We applied this strain measurement technique to two different semiconductor alloy systems using coherently strained epitaxial thin films specifically designed to produce lattice-mismatch strains as small as 10(−4). Comparing our strain sensitivity and signal strength in Al(x)Ga(1−x)As with those obtained using the industry-standard technique of phonon Raman scattering, we found that there was a sensitivity improvement of 200-fold and a signal enhancement of 4 × 10(3), thus obviating key constraints in semiconductor strain metrology.